UNIVERSAL SUFFRAGE DI TENGAH VOLATILITAS DATA PEMILIH: STUDI PEMUTAKHIRAN DATA PEMILIH DALAM PILKADA DKI JAKARTA 2024 - Rizka Yoan Perdana; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
Voter data updating is a crucial instrument in realizing the principle of universal suffrage in electoral administration. This study aims to analyze the extent to which the implementation of voter data updating in the 2024 DKI Jakarta Regional Election was able to guarantee universal suffrage, identify challenges and alleged procedural violations, and analyze the supervisory strategies developed by the DKI Jakarta Provincial Election Supervisory Board (Bawaslu). This study employs an explanative qualitative method with data collected through in-depth interviews with 10 informants (KPU and Bawaslu of DKI Jakarta Province, Pantarlih officers, and voters of the 2024 DKI Jakarta Regional Election) and documentation techniques. The findings indicate that procedurally, voter data updating has sought to guarantee universal suffrage through a layered mechanism, ranging from door-to-door verification to the safety nets of DPTb and DPK. However, substantively, the application of the de jure principle creates gaps whereby ineligible voters risk remaining on the voter list while eligible citizens may be omitted due to inadequate civil registration document updates. High population mobility is the primary source of voter data volatility, accompanied by alleged procedural violations in the field. Bawaslu responded to personnel limitations by developing direct supervisory monitoring and participatory supervision, though their effectiveness remains constrained by weak cadre commitment and the absence of a post-activity monitoring and evaluation system.